Blood monocyte transcriptome and epigenome analyses reveal loci associated with human atherosclerosis - Yongmei Liu (Nature Portfolio, 2017)
The molecular mechanisms mediating the impact of environmental factors in atherosclerosis are unclear. Here, the authors examine CD14+ blood monocyte’s transcriptome and epigenome signatures to find differential methylation and expression of ARID5B to be associated with human atherosclerosis.